Design, Development, And Evaluation Of The E-Tech Lesson Planner For Novice Esl Teachers - Mohamad Fathil, Fadliyana (2022)
This research aimed to create a lesson planning tool for novice ESL primary school teachers in Malaysia, known as E-Tech Lesson Planner (E-Tech LP). E-Tech LP was developed in response to lesson planning issues among novice ESL teachers, particularly the quality of lesson plans produced. Nevertheless, numerous technology-based lesson planning tools in education emphasise efficiency over effectiveness. In developing the prototype, this study employed the Design and Development Research approach (DDR) pioneered by Richey and Klein (2007). The study's first phase involved 232 novice ESL teachers from Northern Region primary schools completing 68-item questionnaires on lesson planning conformity,